Financial difficulty in community-dwelling persons with lower limb loss is associated with reduced self-perceived health and wellbeing. (October 2020) - Lee, Szu-Ping; Chien, Lung-Chang; Chin, Tyler; Fox, Heather; Gutierrez, Juan
Background: Socioeconomic status has been shown to be an important factor in the disparate prevalence and selected treatment of limb loss, but how personal financial difficulty affects patients' health outcomes is currently unclear. Objective: Examining how presence and experience of personal financial difficulty affects perceived health and wellbeing in individuals with lower limb loss. Study Design: Cross-sectional study. Methods: A total of 90 participants (68 males, mean age 58.7 ± 16.7 years) were recruited from local physical therapy and prosthetic and orthotic clinics, rehabilitation hospitals, and a regional amputee patient support group. All participants were community-dwelling, non-military adults with amputation involving at least one major lower limb joint. Participants were interviewed, and each completed a survey that included basic demographic/medical information, self-reported health and wellbeing (Short-Form Health Survey, SF-36v2), and a question to determine their financial situation after limb loss. Multiple regression analyses were used to examine the effect of financial difficulty on the eight subscales of SF-36v2 while accounting for age, gender, and amputation level. Results: Experiencing financial difficulty significantly and negatively affected Role-Physical and Role-Emotional subscale scores ( p < 0.01 and p = 0.02, respectively). Individuals with financial difficulty scored approximately 60% lower in these two specific subscales. Conclusion: Experiencing financial difficulty is a significant predictor for diminished work or daily activity participation due to physical and emotional stresses. Clinicians and health policy makers need to understand how socioeconomic factors may prevent individuals with lower limb loss from achieving higher levels of functional recovery and community re-integration after amputation. Clinical relevance: Our findings showed that presence or experience of financial difficulty was significantly associated with diminished community re-integration in community-dwelling, non-military adults with lower limb loss. It affects both physical and emotional aspects of wellbeing. Clinicians should be aware how socioeconomic factors may affect social re-integration after amputation.